Influencing Factors Affecting Young People’s Attitude Towards Online Advertising: A Systematic Literature Review - De Battista, Ivan; Curmi, Franco; Said, Emanuel (International Review of Management and Marketing, 2021)
Young people are constantly targeted by online advertisements. This systematic literature review aims to identify the principal factors that influence young people’s attitude towards online advertising. It seeks to understand if the influence of online advertising is dependent on gender and age differences in young people. The methodology involves the systematic review of empirical studies published from 1994 to 2020 and identifies the factors that impact young people’s attitude towards online advertising. The review commences with a scoping study and follows the PRISMA structure, which includes identifying studies, screening and evaluation, the analysis and synthesis of studies, and the presentation of the final studies. This work reveals two main observations from a thematic content analysis of the appraised studies. The first relates to the principal factors influencing young people’s attitude towards advertising. These factors comprise informativeness, entertainment, irritation, credibility, personalisation, and interactivity. In general, studies show that when informativeness, entertainment, credibility and interactivity are present, the more positive the attitude towards advertising is, while irritation fosters an unfavourable attitude. Studies provide a dichotomous stand on personalisation. The second relates to young people’s age and gender. Our review notes that earlier studies lack focus on audiences predominantly between 10 and 15 years. Keywords: Attitude towards online advertising, advertising value, young people JEL Classifications: M31, M37 DOI: https://doi.org/10.32479/irmm.11398